2013
DOI: 10.1021/ja407815t
|View full text |Cite
|
Sign up to set email alerts
|

Amplified Halogen Bonding in a Small Space

Abstract: Weak, intermolecular forces are difficult to observe in solution because the molecular encounters are random, short-lived, and overwhelmed by the solvent. In confined spaces such as capsules and the active sites of enzymes or receptors, the encounters are prolonged, prearranged, and isolated from the medium. We report here the application of encapsulation techniques to directly observe halogen bonding. The small volume of the capsule amplifies the concentrations of both donor and acceptor, while the shape of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 34 publications
0
63
0
Order By: Relevance
“…Selective coencapsulation of perfluoropropyl iodide and the XB acceptor pyridine or γ-picoline. 364 receptor and 2,6-dichloropyridine or 2,6-dibromopyridine in toluene ( Figure 101). 365 Since association constants were recorded in the region of 0.2−0.3 M −1 , the authors noted that large numbers of these XB interactions would be required to act in concert to form strong host−guest complexes.…”
Section: Inorganic Halogen-bond Donorsmentioning
confidence: 99%
“…Selective coencapsulation of perfluoropropyl iodide and the XB acceptor pyridine or γ-picoline. 364 receptor and 2,6-dichloropyridine or 2,6-dibromopyridine in toluene ( Figure 101). 365 Since association constants were recorded in the region of 0.2−0.3 M −1 , the authors noted that large numbers of these XB interactions would be required to act in concert to form strong host−guest complexes.…”
Section: Inorganic Halogen-bond Donorsmentioning
confidence: 99%
“…Recently, in an elegant work by Fujita, Metrangolo, and Resnati, the authors highlighted that the confined space inside a self‐assembled cage enhances the halogen bonding between XB donors and XB acceptors. Previously, Rebek also showed that the encapsulation of both XB partners into the nanoconfined space of a dimeric capsule amplified the halogen‐bonding interaction and allowed its NMR characterization.…”
Section: Introductionmentioning
confidence: 99%
“…. Recent studies focus on theoretical as well as experimental investigations of hydrogen/halogen bonds in different confining environments …”
Section: Introductionmentioning
confidence: 99%